Treatment of toxic epidermal necrolysis with intravenous immunoglobulin: a series of three cases Tratamento da necrólise epidérmica tóxica com imunoglobulina endovenosa: uma série de três casos - Cristiane Comparin; Günter Hans Filho; Luiz Carlos Takita; Nayara de Castro Wiziack Costa; Roberta Ayres Ferreira do Nascimento; Lidiane de Oliveira Costa Nanni (Sociedade Brasileira de Dermatologia, 2012)
Stevens-Johnson's syndrome (SJS) and toxic epidermal necrolysis (TEN) are life-threatening dermatoses, that lead to keratinocyte apoptosis induced by interactions between Fas (cell death receptor) and soluble Fas-ligand, present in serum of Stevens-Johnson's syndrome / toxic epidermal necrolysis patients. Anti-Fas antibodies in intravenous immunoglobulin (IVIG) would block the apoptosis cascade. Three cases of toxic epidermal necrolysis occurred in one male and two female patients, after use of allopurinol, leprosy multidrug therapy concomitant with dipyrone, and diclofenac. The cases were treated with intravenous immunoglobulin 2-3 mg/kg and prednisone 20-50 mg/day. The interruption of new lesions outbreak and reepithelization were extremely fast after the use of intravenous immunoglobulin, without adverse effects. Controlled studies are needed to confirm the efficacy of intravenous immunoglobulin in Stevens-Johnson's syndrome / toxic epidermal necrolysis, but the results seem promising. A Síndrome de Stevens-Johnson e a Necrólise Epidérmica Tóxica são dermatoses graves, que levam à apoptose dos queratinócitos induzida pela interação entre Fas (receptor de morte celular) e Fasligante solúvel, presente no soro de pacientes com Síndrome de Stevens-Johnson e Necrólise Epidérmica Tóxica. Anticorpos anti-Fas contidos na imunoglobulina endovenosa podem bloquear esta cascata apoptótica. Três casos de Necrólise Epidérmica Tóxica são descritos, ocorrendo após uso de alopurinol, diclofenaco e poliquimioterapia para hanseníase concomitante com dipirona. Os três casos foram tratados com imunoglobulina endovenosa 2-3 mg/kg, divididos em 4 ou 5 dias e prednisona 20-50 mg/dia. A interrupção no surgimento de novas lesões e a repitelização foram extremamente rápidas, sem ocorrência de efeitos adversos. Estudos controlados são necessários para confirmar a eficácia da imunoglobulina endovenosa na Síndrome de Stevens-Johnson e Necrólise Epidérmica Tóxica, porém, seus resultados parecem ser promissores.